Presenting a Statistical Model of Fatigue Prediction for the Effect of Loading Frequency on Reflective Cracks Propagation on Asphalt Layers Improved by Geosynthetics - Saeid Asadi; Gholamali Shafabakhsh (Journal of Rehabilitation in Civil Engineering)
So far, several methods have been proposed for delaying the reflective cracks in pavements. Despite substantial money spent annually on these types of maintenance methods to control reflection cracking in road pavement, none of them has successfully prevented such damage and only delayed crack propagation in improved asphalt overlays. However, some of these methods have been more effective in preventing the initiation of reflective cracks and reducing the severity of their damage in restored pavements. One of the best methods to deal with this issue is using geosynthetic products. The present study investigates the performance of two different types of geocomposites in the reinforcement of asphalt overlays in delaying reflective cracks compared to control samples. To this end, laboratory and statistical studies were performed at different temperatures and loading frequencies. The results showed that using type-I geocomposite will be most effective in increasing fatigue life. On the other hand, among the mentioned factors, the temperature rise will have the most negative effect on the fatigue performance of geocomposite layers in asphalt overlays. Finally, a high-accuracy statistical model of fatigue life based on temperature, frequency, and geocomposite type is presented (i.e., R² and Adjusted R² of 0.987 and 0.981, respectively).